Utilization of laser-assisted analytical methods for monitoring of lead and nutrition elements distribution in fresh and dried Capsicum annuum l. leaves - Galiová, Michaela; Kaiser, Jozef; Novotný, Karel; Hartl, Martin; Kizek, Rene; Babula, Petr (Microscopy research and technique, 2011)
Laser induced breakdown spectroscopy (LIBS) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) have been applied for high-resolution mapping of accumulation and distribution of heavy metal (lead) and nutrition elements (potassium, manganese) in leaves of Capsicum annuum L. samples. Lead was added in a form of Pb(NO₃)₂ at concentration up to 10 mmol L⁻¹ into the vessels that contained tap water and where the 2-months old Capsicum annuum L. plants were grown another seven days. Two dimensional maps of the elements are presented for both laser-assisted analytical methods. Elemental mapping performed on fresh (frozen) and dried Capsicum annuum L. leaves are compared.
Keywords: Manganese; Image Processing, Computer-Assisted; draslík; Lead; elemental mapping; Potassium; Capsicum; spektrální analýza; olovo; počítačové zpracování obrazu; Plant Leaves; laserová terapie; LIBS; listy rostlin; Laser Therapy; mangan; Spectrum Analysis; LA-ICP-MS